Studi Visualisasi Dan Bibliometrik Pada Volatilitas Pasar Kripto - Anak Agung Ary Anila Kusuma Wardani (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
Cryptocurrency market volatility has been an interesting topic of research in recent years. Previous studies have shown that crypto market volatility affects investment risk levels and crypto asset price movements. In this study, the author used visualization and bibliometric analysis to further understand cryptocurrency market volatility. The bibliometric analysis results showed that research on crypto market volatility continues to grow and is widely conducted by researchers from the range of 2017 to 2023. The most common research themes related to financial markets, cases, volatility spillovers, and cryptocurrency volatility. From the research results, it can be concluded that cryptocurrency market volatility is a topic of interest to many researchers. Factors that influence crypto market volatility, such as political events, regulations, and blockchain technology adoption, are the main focus of research in this field.